On the investigation of an economic value for forest ecosystem services in the past 30 years: Lessons learnt and future insights from a North–South perspective - Pisani, Domenico; De Lucia, Caterina; Pazienza, Pasquale (Frontiers in Forests and Global Change, 2022)
Since the publication of the Millennium Ecosystem Assessment (MA) (2005), the research of ecosystem services valuation has seen an exponential growth with a consequent development, improvement, and spread of different qualitative and quantitative methods. The interest is due to the benefits that ecosystem services provide for human wellbeing. A large part of ecosystem services is provided by the so-called forest ecosystem services (FES) in both protected and non-protected areas. The aim of the present study is to investigate key variables driving the FES value at global level. These include, other than socio-economic information, the ecosystem services’ quality condition and the location of the study. The research uses a meta-regression of 478 observations from 57 studies in the time span 1992-2021 retrieved from the online Ecosystem Service Valuation Database (ESVD). Main results show that both the ES quality condition and spatial aspect are relevant factors in determining the estimated value of FES, suggesting the existence of a difference in the forest value from a North-South perspective. The investigation of an economic assessment of FES is advised as a key research trend in the immediate future. This allows to close the gap between the global North and South and favours the implementation of adequate socio-economic and environmental governance for an efficient forest management.